MANAJEMEN HAFALAN AL-QUR’AN DENGAN STRATEGI EFEKTIF DALAM MENGELOLA HAFALAN SECARA BERKELANJUTAN - Ramlan Sa'at; Zainal Efendi Hasibuan (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2025)
Memorizing the Qur'an is a religious activity that combines spiritual, cognitive, and affective aspects. Success in memorizing and maintaining the Qur'an depends on systematic management and appropriate strategies. This article discusses Qur'ānic memorization management strategies from various aspects, including memorization methods, scheduling memorization and murojaah, the role of mentors and the environment, and the integration of digital technology. Using a qualitative desk study approach, the article analyzes various practices implemented by Qur'ānic memorizers in pesantren, tahfidz houses, and independently. The study shows that integrated and sustainable strategies can increase the effectiveness and durability of memorization, while supporting the improvement of the quality of worship and spiritual closeness to the Qur'an.